Mental Healthy Literacy of Teachers: a Systematic Literature Review - Padmi Dhyah Yulianti; Endang Retno Surjaningrum; Dwi Yuwono Puji Sugiharto; Nurul Hartini (Journal of Educational, Health and Community Psychology, 2021)
School is a protective factor to improve and promote mental health. Many mental health problems are experienced by school learners. From various interactions with the learners, teachers are expected capable to prevent and identify school learnersâ€™ mental health problems. Although the human-teacher sources are high but they are not completely used to support learnersâ€™ mental health problems. This research aims to find out the mental health literacy operational definition and the urgency of mental health literacy of the teachers. This research applied a systematic literature review from five search engines. They were Spingerlink, Science Direct, Jstor, Eric, and Pubmed. The applied keywords were â€œmental health literacyâ€, â€œschoolâ€, and â€œteacherâ€. The taken references are from 1997 - 2020. Â Six hundred and thirty three articles were obtained from five search engines. Â From the systematic review, seven articles were obtained.Â  An expanding concept of mental health definition was found from the initial concept proposed by Jorm. Clear concept definition influenced the measurement. Teachers must be aware of mental health literacy because they are the first lines to identify mental health problems of the learners, mostly found on 12 - 25 years-old learners. Low teacher literacy at school about mental health problems experienced by learners led to serious impacts for them.